Defeating SAD (seasonal affective disorder) : a guide to health and happiness through all seasons - Rosenthal, Norman E. (G&D Media, 2023)
Rosenthal, who first described Seasonal Affective Disorder (SAD) and is the foremost authority on the subject, offers an up to date guide to overcoming the miseries and that millions experience with the changing seasons. In his lively style, Rosenthal offers advice on how to identify, treat and overcome both winter and summer varieties of seasonal affective disorder, as well as the less severe yet bothersome winter blues.